Comparing the Effects of Manual and Self-exercise Therapy for Improving Forward Head Posture - Gyeongseop Sim; Donghoon Kim; Hyeseon Jeon (Korean Research Society of Physical Therapy, 2023)
Background: Studies investigating the immediate effects of a single intervention to correct forward head posture are rare. Objects: This study aimed to compare the changes in treatment effects in patients with forward head posture and neck pain after manual and self-exercise therapy over a 1-hour period. Methods: Twenty-eight participants were randomly divided into manual and self-exercise therapy groups. Following the initial evaluation, manual or self-exercise therapy was applied to each group for 30 minutes each in the prone, supine, and sitting positions. The variables measured were the craniovertebral angle (CVA), stress level, pain level, and sternocleidomastoid (SCM) stiffness. After the intervention, re-evaluation was conducted immediately, 30 minutes later, and 1 hour later. Two-way analysis of variance (ANOVA) was used to compare the maintenance of treatment effects between the two groups. Results: Based on the two-way mixed ANOVA variance, there was no interaction between the groups and time for all variables, and no main effects were found between the groups. However, a significant effect of time was observed (p < 0.05). Post hoc tests using Bonferroni's correction revealed that in both groups, the CVA, pain, and stress showed significant improvements immediately after the intervention compared with before the intervention, and these treatment effects were maintained for up to 1 hour after the treatment (p < 0.0083) in the manual therapy group. However, the stress level was maintained until 30 minutes later (p < 0.0083) in the self-exercise group. There was no significant decrease in right SCM stiffness before and after the intervention; however, left SCM stiffness significantly decreased after the self-exercise intervention (p < 0.0083). Conclusion: Both manual and self-exercise therapy for 30 minutes were effective in reducing forward head posture related to the CVA, pain, and stress levels. These effects persisted for at least 30 minutes.